1998
DOI: 10.1104/pp.116.3.1043
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Microtubule/Microfibril Paradigm1

Abstract: The cortical microtubule array provides spatial information to the cellulose-synthesizing machinery within the plasma membrane of elongating cells. Until now data indicated that information is transferred from organized cortical microtubules to the cellulosesynthesizing complex, which results in the deposition of ordered cellulosic walls. How cortical microtubules become aligned is unclear. The literature indicates that biophysical forces, transmitted by the organized cellulose component of the cell wall, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(39 citation statements)
references
References 32 publications
5
34
0
Order By: Relevance
“…However, studies of the conditional mor1 mutant of Arabidopsis, which is deficient in microtubule polymerization at the nonpermissive temperature, have shown that ordered cellulose deposition is possible in the absence of assembled cortical microtubules and an existing cellulose template (51,52). It has also been observed that treatment of protoplasts with the cellulose synthase inhibitor isoxaben prevents characteristic orientation of the microtubules demonstrating cell wallto-cytoskeleton feedback (53). We believe that these seemingly contradictory lines of evidence may reflect a variable relationship between the cytoskeleton and the cellulose synthase complexes, depending on the stage of cell wall synthesis and expansion.…”
Section: Control Synthesis and Assemblymentioning
confidence: 96%
“…However, studies of the conditional mor1 mutant of Arabidopsis, which is deficient in microtubule polymerization at the nonpermissive temperature, have shown that ordered cellulose deposition is possible in the absence of assembled cortical microtubules and an existing cellulose template (51,52). It has also been observed that treatment of protoplasts with the cellulose synthase inhibitor isoxaben prevents characteristic orientation of the microtubules demonstrating cell wallto-cytoskeleton feedback (53). We believe that these seemingly contradictory lines of evidence may reflect a variable relationship between the cytoskeleton and the cellulose synthase complexes, depending on the stage of cell wall synthesis and expansion.…”
Section: Control Synthesis and Assemblymentioning
confidence: 96%
“…Immunodetection in protoplasts was done as described in Fisher and Cyr (Fisher and Cyr, 1998). Rat Jim5 and anti-rat Cy3 (Santa Cruz Biologicals, CA) were used at 1:100.…”
Section: Immunodetectionmentioning
confidence: 99%
“…In expanding plant cells, the cellulose-xyloglucan network is considered the main load-bearing network that controls the extent of cell expansion, whereas the orientation of cellulose microfibril deposition has a major role in controlling the direction of cell expansion (Fisher and Cyr, 1998). After a period of expansion, certain cell types lay down a thick secondary cell wall inside the primary wall.…”
Section: Introductionmentioning
confidence: 99%